Globalization and Employment: The Impact of Trade on Employment Level and Structure in the Philippines - Aniceto C. Orbeta (Philippine Institute for Development Studies (PIDS), 2002)
This paper presents one of the few empirical estimates of the impact of globalization, here represented by trade flows, on employment level and structure using Philippine data. Using both aggregate and sub-industry level manufacturing data, the paper shows that increases in the propensity to export shifts the demand for labor upward. It also shows that the impact of the propensity to import on labor demand is unclear yielding from significantly positive to insignificant coefficients. In terms of employment structure, the impact of openness on the proportion of women workers is not significant in the aggregate but at the manufacturing sub-industry level, the increase in the propensity to export is a boon for women workers. Finally, increases in export propensity increase the proportion of low-skilled production workers both at the aggregate and manufacturing sub-industries level.
Keywords: 330; globalization; employment opportunities; trade and pollution; Globalisierung; Außenhandelselastizität; Beschäftigungseffekt; Philippinen